PENGARUH STRATEGI PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HIGH ORDER THINKING SKILLS (HOTS) SISWA PADA PEMBELAJARAN MATEMATIKA DI MADRASAH IBTIDAIYAH - Mariati, Ari (Sasangga: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to analyze the impact of the Contextual Teaching and Learning (CTL) strategy on students' High Order Thinking Skills (HOTS) in mathematics learning in fifth-grade students at MI Nahdatussibyan, Barito Kuala. The study is motivated by the low-level thinking skills of students, reflected in their difficulty solving mathematics problems that require analysis, synthesis, and evaluation. To address this, CTL was implemented to connect mathematics learning with real-life contexts. This research employed a quasi-experimental method with a one-group pretest-posttest design. The subjects were 30 fifth-grade students at MI Nahdatussibyan. Data were collected through HOTS tests administered before and after the CTL intervention. The data were analyzed using a t-test to determine the significance of the difference between pretest and posttest scores. The results showed a significant increase in students' HOTS. The average HOTS score increased from 65 on the pretest to 85 on the posttest. Improvements were observed in the three main HOTS aspects: analysis, synthesis, and evaluation. These findings demonstrate that the CTL strategy effectively enhances students' active engagement in learning and improves their higher-order thinking skills